2018
DOI: 10.6018/analesps.34.2.293101
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Spanish version of the 12-item Interpersonal Needs Questionnaire in fibromyalgia syndrome patients

Abstract: According to the interpersonal theory of suicide, thwarted belongingness and perceived burdensomeness are key elements in the development of suicidal ideation. The Interpersonal Needs Questionnaire (INQ) was developed to assess the degree of frustration of these two interpersonal needs related to suicidal ideation. This study aims to analyze the psychometrics properties of a Spanish adaptation of INQ-12 in fibromyalgia patients. Exploratory factor analysis (n = 180) and confirmatory factor analysis (n = 179) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
(58 reference statements)
0
4
0
2
Order By: Relevance
“…Interpersonal Needs Questionnaire (INQ-10; [ 60 ]) adapted to Spanish [ 61 ]. This self-administered 10-item questionnaire evaluates perceived burdensomeness (first six items) and thwarted belongingness (last four items).…”
Section: Methodsmentioning
confidence: 99%
“…Interpersonal Needs Questionnaire (INQ-10; [ 60 ]) adapted to Spanish [ 61 ]. This self-administered 10-item questionnaire evaluates perceived burdensomeness (first six items) and thwarted belongingness (last four items).…”
Section: Methodsmentioning
confidence: 99%
“…Foi observada ainda uma relação entre maior frequência de ideações suicidas e a FM, havendo o risco de suicídio pela sensação de sobrecarga, não pertencimento e desesperança nos pacientes, devido aos sintomas da doença. Percebeu-se relação direta de ideação suicida com severidade e duração da dor (Ordoñez-Carrasco et al, 2018). Variáveis sociais também foram citadas, como o apoio social negativo, que teve correlação positiva quando relacionado à depressão, baixando os níveis da mesma e melhorando os sintomas conforme a pessoa tem mais interações sociais (Freitas, Andrade, Spyrides, Micussi & Sousa, 2016), sendo paradoxal com o fato de que a depressão é preditora de dificuldades nas relações sociais (Horta-Baas & Romero-Figueroa, 2019).…”
Section: Depressãounclassified
“…A ansiedade foi o segundo tema mais citado na revisão, sendo citada em oito artigos (Moretti, Silva & Novoa, 2018;Goulart, Pessoa & Lombardi-Junior, 2015;Dias, Marques, Bettini e Paiva, 2017;Terzi, Terzi & Kale, 2015;Sarudiansky, 2016;Işık-Ulusoy, 2019;Cabrera, Martín-Aragón, Terol, Núñez & Pastor, 2015;Macedo, Martins-Silva, Gavi & Macedo, 2015). Ela é ligeiramente menos presente do que a depressão nos pacientes (Danet, Prieto-Rodríguez, Valcárcel-Cabrera & March-Cerdà, 2016), mas é importante destacar, conforme observado em três estudos (Goulart, Pessoa & Lombardi-Junior, 2015;Terzi, Terzi & Kale, 2015;Sarudiansky, 2016), que os pacientes com FM são mais ansiosos que a população & Salvetti, 2018;Dias, Marques, Bettini e Paiva, 2017;Alves, Zakka, Teixeira, Kaziyama, Siqueira & Siqueira, 2016;Terzi, Terzi & Kale, 2015;Sarudiansky, 2016;Horta-Baas & Romero-Figueroa, 2019;Işık-Ulusoy, 2019;Cabrera, Martín-Aragón, Terol, Núñez & Pastor, 2015;Ordoñez-Carrasco, Salgueiro, Sayans-Jiménez, Blanc--Molina, García-Leiva, Calandre & Rojas, 2018;Macedo, Martins-Silva, Gavi & Macedo, 2015). Os estudos demonstraram relação entre a depressão e a FM quando comparados a grupos controle sem doenças crônicas, pontuando escores mais altos em diversos instrumentos psicológicos.…”
Section: Ansiedadeunclassified
“…The successive incidents of suicides and deaths of migrant workers have drawn particular attention to the psychological conditions of young migrant workers on the production line [ 4 ]. In past studies, there have been several versions of the INQ, including 10-, 12-, 15-, and 25-item questionnaires [ 14 , 24 , 26 , 37 , 38 ], whereas Hill et al recommended using the 15- or 10-item versions because these versions indicated the most consistent model fit in confirmatory factor analyses [ 39 ]. In this study, we primarily used the INQ-15 recommended by the Van Orden K.A.…”
Section: Introductionmentioning
confidence: 99%